The Impact of Uncertainty on Pedestrians’ Decision to Start Roadway Crossing during the Clearance Phase - Milan Simeunović; Andrijana Jović; Pavle Pitka; Mladen Dobrić (Complexity)
Clearance phase at signalized crosswalks is an important parameter of pedestrians’ safety because it helps them to complete the crossing before the green signal for vehicles. However, there is the issue of pedestrian decision as to whether to cross if they arrive at the crosswalk during the clearance phase, which represents a violation in many countries. Due to the proof that pedestrian violations multiply the risk of traffic accidents, in this study, the tendency of pedestrians to commit violations during the clearance time has been researched. With the aim of proposing the design of the pedestrian traffic lights, which could decrease the frequency of pedestrian violations, the comparison of pedestrians behaviour at crosswalks with and without a countdown timer during the clearance time was made, based on the data collected in the video recording. Chi square independency test showed that there is a statistically significant difference in the behaviour of pedestrians during the clearance time, depending on the existence of the timer, as well as the fact that pedestrians behave in a safer manner if there is no clearance time shown on the timer. The total delay rate on the roadway during the red signal, which was the consequence of starting the crossing during the clearance time or subsequent violations, was 1.3 times higher at the crosswalks with the countdown timer. This research was unique because for the first time, two-phase pedestrian crossings on the roadway with the median refuge island in the sense of clearance time were analysed, in spite of the previous proof that pedestrians are more likely to commit violations during the red signal in that kind of roadway. Another novelty in the research was pedestrians following till the end of crossing, due to the possibility of subsequent violations. With the means of binary logistic regression, different factors which affect pedestrians’ behaviour during the clearance time have been determined and they differ depending on the existence of the timer. At the pedestrian crosswalks with the timer, contributing factors have been determined, such as gender, the number of waiting pedestrians, distractions, arrival time, and age. If there is no timer, the contributing factors are the following: the number of crossing pedestrians, distractions, group, position of pedestrians in relation to the vehicle, the number of traffic lanes, and age. Based on the obtained results, a new design of the pedestrian traffic lights was proposed.